German Universities Open Doors to Refugees: Access Barriers Remain - Morris-Lange, Simon; Brands, Florinda (International Higher Education, 2016)
In the face of unprecedented numbers of asylum seekers, German universities are inviting newcomers to enroll in their tuition-free study programs. However, so far only a handful of asylum seekers can be found in lecture halls across the country as legal and financial barriers condemn thousands of young and eager men and women to months and even years of idleness.